S144. SUBJECTIVE LANGUAGE APTITUDE IS LINKED TO NEURAL ACTIVITY IN LANGUAGE AREAS, BUT NOT TO BEHAVIORAL OUTCOME. (18th May 2020) - Sabrina Zengaffinen, Francilia; Stahnke, Antje; Furger, Stephan; Federspiel, Andrea; Koenig, Thomas; Stegmayer, Katharina; Walther, Sebastian; Wiest, Roland; Strik, Werner; Dierks, Thomas; Morishima, Yosuke
Abstract: Background: In mental illnesses, the language domain, including speech and thought, is often affected. The spectrum of language symptoms shows a great variability between patients with psychosis. In previous studies, we have not only demonstrated that patients and healthy controls show activation differences in the neural language circuitry, but also within the different patient groups. The Bern psychopathology scale is a tool to help differentiate patients, which presents with disinhibited or inhibited language symptoms. This aids to examine the continuum from health to psychosis in a dimensional approach. To understand the bipolarity within the patient groups on the continuum of language domain, the healthy population needs to be examined as well. Therefore, in the current study, a healthy population was tested to investigate this heterogeneity in the language domain during a lexical decision task. Additionally, a subjective rating of one's language aptitude was measured, to gain an insight on where they would see themselves on the continuum. The aim was to examine the spectrum of inter-individual differences and its association with language-related brain networks, specifically Broca's and Wernicke's area. This observed heterogeneity of a healthy population would allow an extrapolation to clinical ends of the spectrum. Methods: While measuring brain activity with fMRI, 102 healthy adult subjects performed a lexical priming task. Subjects had to decide if a visually presented target word would form the generic term of a previously shown prime word, in terms of its relation (e.g. Dog – Cat) or its category (e.g. Dog – Animal). To group the participants, each subject rated their own language aptitude on 7-point Likert scale. According to their rating they were then sorted into high, mid or low language aptitude groups. Results: Although, we found differences in brain activation in Broca (BA44/ BA45) and Wernicke (pMTG) among the groups, the behavioral outcome, specifically reaction time (RT) and accuracy, showed no significant differences between the groups. We studied the activation patterns in the region of Broca's area (BA45, BA44) and Wernicke's area (pMTG) during preparation (waiting for the target after the indication of task type) and processing (target word processing) phases. We found group differences in BA45 during both preparation and processing phases. The Post hoc analysis revealed that the high group showed significantly greater activation in BA45 compared to the low group. While BA44 and pMTG showed only a significant group difference during the processing phase. Also, here the Post hoc analysis revealed that the high group showed greater activation in both areas during the processing phase. Furthermore, the psychophysiological interaction (PPI) analysis of BA44, during preparation phase, with RT as covariate revealed distinct functional connectivity patterns from seed area BA44 among the high and low language aptitude groups. We found, that a stronger connectivity from BA44 to the left posterior middle temporal gyrus (pMTG) was related with faster RT in the high group. The low group showed a same pattern from BA44 to the left fusiform gyrus, also known as the visual word form area. Discussion: These results indicate that, one utilizes the language-related brain areas differently, as well as their connectivity, during the language task according to the subjective evaluation of oneself language aptitude. These new insights into the dimension of language is facilitating further research in psychosis, that analyzes the continuum from the healthy population profiles to the profiles of the population with psychosis. With this, it supports the efforts to improve diagnostic tools and treatment options for patients with psychosis.